Spontaneous soliton formation in a region of vibration-rotation transition of molecular multi-component media; 12th Symposium and School on High-Resolution Molecular Spectroscopy, June 3, 1997, St. Petersburg, Russia - Kistenev Yu. V. (1997, 1997)
Title screen